2016
DOI: 10.2166/wp.2016.009
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of water consumption in multipurpose reservoirs

Abstract: The Intergovernmental Panel on Climate Change Special Report on Renewable Energy Sources represented a benchmark in the assessment of water consumption from electricity production. The numbers for hydropower ranged from very low to much larger than the other renewable technologies, partly explained by methodological problems. One of the methodological shortcomings identified was the lack of guidance on how to allocate the water consumption rates in multipurpose reservoirs. This paper is, according to the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…Choice of allocation method is a known problem from Life Cycle Assessment (LCA)‐based studies, and the basis for allocation in LCA‐studies is often ISO Standard 14044 . According to the authors' knowledge, the study by Bakken et al was the first of its kind that systematically tested out allocation methods as specified by ref. .…”
Section: Dilemmas Related To the Applied Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Choice of allocation method is a known problem from Life Cycle Assessment (LCA)‐based studies, and the basis for allocation in LCA‐studies is often ISO Standard 14044 . According to the authors' knowledge, the study by Bakken et al was the first of its kind that systematically tested out allocation methods as specified by ref. .…”
Section: Dilemmas Related To the Applied Methodologymentioning
confidence: 99%
“…The study tested four different allocation methods in four multipurpose reservoirs, all serving three to five functions, and concluded that volume allocation was the most feasible and robust approach. Economic allocation was found by Bakken et al to be sensitive to selection of economic valuation method, but acknowledged that this method could be useful in those cases where the same economic valuation method was applied across all functions served by the reservoir. Kadigi et al underline that use of economic valuation methods could underestimate the social value of water.…”
Section: Dilemmas Related To the Applied Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalent generation technologies include coal, solar PV, wind, hydro and so on. This study does not consider hydropower because the quantification of its water use embodies many methodological disputes and uncertainties, especially regarding the attribution of water use in multi-purpose reservoirs (Bakken et al 2016). In terms of cooling technologies in thermoelectric power plants, air cooling systems, which use air to cool down the steam exiting turbines, use the least water.…”
Section: Introductionmentioning
confidence: 99%